2018
DOI: 10.1371/journal.pone.0201540
|View full text |Cite
|
Sign up to set email alerts
|

Liver and intestinal protective effects of Castanea sativa Mill. bark extract in high-fat diet rats

Abstract: The effects of Castanea sativa Mill. have been studied in high fat diet (HFD) overweight rats. Natural Extract of Chestnut bark (Castanea sativa Mill.) (ENC®), rich in ellagitannins, has been studied in 120 male Sprague-Dawley rats, divided in four groups. Two groups were controls: regular (RD) and HDF diet. Two groups received ENC® (20 mg/kg/day): RD + ENC® and HFD + ENC®. At baseline and at 7, 14 and 21 days, weight gain, serum lipids, plasma cytokines, liver histology, microsomial enzymes and oxidation, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Some spices and vegetal extracts exert antioxidant [ 9 ] and hypocholesterolemic effects [ 11 , 12 ]. Saffron ( Crocus sativus L.) is one of the most popular spices [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some spices and vegetal extracts exert antioxidant [ 9 ] and hypocholesterolemic effects [ 11 , 12 ]. Saffron ( Crocus sativus L.) is one of the most popular spices [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of this plant have displayed a clear biological activity; in particular, they have shown cardioprotective [2], antihelminthic, antibacterial, and antiviral effects [3] and neuroprotective activity [4]. Observations recently made by Budriesi et al [5] in high-fat diet rats suggested that the chestnut extract has the potential to be used in medicine as a dietary supplement in the treatment of obesity complications.…”
Section: Introductionmentioning
confidence: 99%
“…Plant origin preparations were also investigated as to their potential to prevent pathological processes connected with obesity. This direction seems to be of great importance as obesity and related disturbances, resulting from sedentary lifestyle as well as excessive consumption, are becoming more and more serious world problem [ 132 , 133 ]. Diet-induced obesity was found to be connected with different disturbances of various parameters including liver markers and lipid profile as well as inflammation, lipogenesis, and oxidative balance.…”
Section: The Protective Properties Of Plant Preparations Against Tmentioning
confidence: 99%
“…Diet-induced obesity was found to be connected with different disturbances of various parameters including liver markers and lipid profile as well as inflammation, lipogenesis, and oxidative balance. The performed research revealed the protective effect of plant preparations which involved improvement of oxidative balance by activation of the Nrf2/HO-1 antioxidant pathway [ 61 ] and the ameliorating effect on lipid status [ 132 , 133 ]. The latter was also confirmed in vitro as the lipolysis-promoting influence in 3T3-L1 cells was observed [ 61 ].…”
Section: The Protective Properties Of Plant Preparations Against Tmentioning
confidence: 99%